The Dampening Effects of Perceived Teacher Enthusiasm on Class-Related Boredom: The Mediating Role of Perceived Autonomy Support and Task Value - Cui, Guanyu; Yao, Meilin; Zhang, Xia (Frontiers in Psychology, 2017)
Class-related boredom is commonly experienced by students and it has an impact on their learning engagement and achievements. Previous research has found that perceived teacher enthusiasm might contribute to reducing students’ class-related boredom. However, the mechanism through which perceived teacher enthusiasm affects class-related boredom remains unexplored. The purpose of the present study was to investigate the mediating role of perceived autonomy support and task value in the relationship between teacher enthusiasm and class-related boredom. College students (N = 734) completed questionnaires on perceived teacher enthusiasm, boredom proneness, perceived task difficulty, perceived autonomy support, perceived task value, and class-related boredom. Results showed that after controlling for the effects of demographic variables, boredom proneness, and perceived task difficulty, both perceived autonomy support and task value fully mediated the relationship between perceived teacher enthusiasm and class-related boredom. These findings suggest that students who perceive more teacher enthusiasm might perceive more autonomy support and task value, which in turn reduce the students’ class-related boredom. Limitations in the present study have also been discussed.